Linguistic Complexity in Hadith: An Examination of the Role and Origins of 'Al-kalimat al-mubtakirah' in Hadith - Machsun, Mohamad Anang Firdaus (UIN Sunan Kalijaga Yogyakarta, 2023)
This research investigates an intriguing phenomenon concerning the use of the Arabic language in the narrations of Hadith. Despite Prophet Muhammad's acknowledged fluency in the Arabic language, there are instances of foreign words, known as